Prostacyclin inhibits adhesion of polymorphonuclear leukocytes to human vascular endothelial cells due to adhesion molecule independent regulatory mechanisms - Lindemann, Stephan; Gierer, Claudia; Darius, Harald (Basic research in cardiology, 2003)
Prostacyclin is an important endothelial mediator involved in the interaction of neutrophils (PMN) with the vessel wall. Many studies have shown the beneficial effects of prostacyclin in ischemia and reperfusion. However, no previous study has investigated the direct effects of the prostacyclin analogs iloprost (ILO) and alprostadil (PGE(1)) on the endothelial part of the adhesion process. Human umbilical vein endothelial cells (HUVECs) were grown to confluence, stimulated with 300 U/ml TNF-alpha and treated with increasing concentrations of ILO and PGE(1). The cells were washed to remove TNF and the inhibitors and adhesion of fluorescence-green labeled PMN was determined microscopically. ICAM-1, VCAM-1 and E-selectin expression were measured by a cell-surface ELISA. The chemoattractant activity of the endothelial cell releasate was tested in a Boyden chamber.ILO and PGE(1) reduced PMN-adhesion in a concentration-dependent manner (ILO: -54 +/- 9 % at 0.5 microM, PGE1: -46 +/- 10 % at 10 microM). However, the surface expression of ICAM-1, VCAM-1 and E-selectin remained unaltered. When the supernatant of iloprost/PGE(1)-treated cells was transferred onto cells that were activated, but not treated with ILO or PGE(1), the reduction of PMN adhesion remains sustained. These data indicate that the inhibitory effect of ILO/ PGE(1) treatment is achieved by a reduced chemoattractant potential. PAF-antagonists were able to block neutrophil adhesion and mimicked the effect of ILO, while exogenous PAF diminished the inhibitory effect of ILO concentration-dependently. This study demonstrates the beneficial effects of ILO and PGE(1) on inflammatorily activated endothelial cells. These prostacyclin analogs inhibit PMN-adhesion despite maximal adhesion molecule expression by regulating the balance of - yet to be determined - endothelial-derived mediators.